Propuesta metodológica para fomentar la expresión escrita, en los estudiantes de 4to “A” de la Unidad Educativa Pío Jaramillo Alvarado, Loja 2023-2024 - Ríos Pogo, Karen Mayerli (2024)
The Curricular Integration Work titled "Methodological Proposal to Promote Written Expression in 4th-grade students 'A' at Pío Jaramillo Alvarado Educational Unit, Loja 2023- 2024" has the general objective of designing a methodological proposal to strengthen written expression in 4th-grade students 'A' at the Pío Jaramillo Alvarado Educational Unit, Loja, during the academic period 2023-2024. This research is descriptive, with a mixed approach and a quasi-experimental design. The theoretical framework addresses topics related to methodological strategies and written expression. Scientific, analytical, synthetic, statistical, and descriptive methods were employed during the investigative process. Information was collected through an interview with the teacher and the application of the Ricardo Olea test to students. The investigated population includes thirty students and one teacher from the Pío Jaramillo Alvarado Educational Unit. The results allowed determining that a high percentage of the investigated students present a mild level of written expression, while a lower percentage has a moderate level of written expression. To improve these results, the "Expressive Peques" proposal was designed and successfully implemented. Its effectiveness was confirmed with the second application, and data presented in a comparative table highlight significant changes. Therefore, it is concluded that the application of selected methodological strategies constitutes an effective pedagogical tool to promote written expression in students.